Does Age Impact on Expectations and Concerns of Patients Attending a Chronic Pain Clinic?. Issue 1 (20th November 2017) - McLoughlin, Margaret; Imran, Ather; Hannigan, Ailish; Harmon, Dominic
Abstract: Background: Recognizing expectations and concerns of patients leads to more specialized management plans and greater adherence to treatment and improves outcomes. Little is known about how age impacts on expectations or concerns regarding pain in patients attending a chronic pain clinic. Methods: We prospectively assessed the expectations and concerns of 100 adult patients at their first visit to a pain clinic. Patients reported their expectations and concerns for the clinic visit using a self‐completed questionnaire. Categories of concerns and expectations were compared across age groups (≤ 65 years, > 65 years) using the chi‐square test and Fisher's exact test. Results: Thirty‐nine patients (39%) were over 65 years of age (older patients). The most frequently stated site of pain was the lumbar spine for all patients regardless of age. Common concerns of all patients related to sleep and mobility, and the most common expectation related to analgesia. Younger patients were more concerned about employment (23% vs. 3% of older patients, P = 0.005) and social participation (21% vs. 5%, P = 0.03), whereas older patients were more likely to be concerned about mobility (46% vs. 15% of younger patients, P = 0.001). More younger patients expected education on the source of pain than did older patients (23% vs. 3%, P = 0.005), whereas older patients were more likely to be unsure or have no expectations (26% vs. 3%, P = 0.005). Conclusion: We found differences in patient expectations and concerns by age of those attending a chronic pain clinic. These differences can inform the communication process between physician and patient on treatment plans and outcomes.